COMBINED DISASTER EMERGENCY RESPONSE MANAGEMENT SIMULATION TRAINING - Rahmawati, Ika (Institut Ilmu Kesehatah Bhakti Wiyata Kediri, 2025)
Disasters are events that often result in the loss of property, lives, and environmental damage. Disasters can happen to anyone and often occur when people are unprepared, leading to significant casualties. Community empowerment can increase capacity to face disasters. It is crucial for communities living in disaster-prone areas to better prepare themselves to minimize the impact of disasters. The joint simulation activity for disaster emergency response management is an effort to enhance preparedness in facing disasters. This community service activity was successfully held from September 28 to October 28, 2023, at the Manisrenggo Sub-District Field in Kediri City and was attended by 165 participants. The event was organized by the Bhakti Wiyata Institute of Health Sciences Kediri in collaboration with the Indonesian Red Cross (PMI), Bapena PPNI, Non-Governmental Organizations (NGOs), and educational institutions in Kediri City. After conducting assessments and coordination at the site, preparations for tools and materials were made, followed by the implementation of the community service program. The activity began with socialization on disaster management, which was then followed by disaster simulation activities. Through this program, the community expressed 100% satisfaction and happiness, as they gained additional knowledge about disaster management, making them better prepared to face disasters. The community was fully satisfied with the community service program that had been carried out.Â